Amino-functionalized MOF gel mixed matrix membrane for efficient carbon dioxide separation as well as preparation method and application of amino-functionalized MOF gel mixed matrix membrane

By combining amino-functionalized MOF gel with a polymer matrix to prepare a mixed matrix membrane, the performance and stability problems of traditional membrane materials in CO2 capture are solved, and efficient CO2 separation performance and mechanical stability are achieved, which is suitable for Industrial applications.

CN119327237AInactive Publication Date: 2025-01-21HUNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411449450.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional membrane materials have defects in gas separation performance and long-term stability, which are difficult to meet the needs of efficient separation in industrial applications, especially in CO2 capture.

Method used

By introducing amino-functionalized metal organic framework gel (MOF-NH2 gel) and combining it with the polymer matrix to prepare mixed matrix membranes (MMMs), the dispersion and compatibility of MOF materials are enhanced and a more uniform dispersion structure is formed. Thereby improving the selective adsorption capacity and permeability of CO2.

Benefits of technology

It significantly improves the selective adsorption capacity and permeability of CO2, improves the mechanical strength and stability of the membrane, allowing it to maintain excellent separation performance over long periods of use and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327237A_ABST
    Figure CN119327237A_ABST
Patent Text Reader

Abstract

The invention provides an amino-functionalized metal organic framework gel (MOF-NH2gel) mixed matrix membrane (MMMs) for high-efficiency carbon dioxide separation and a preparation method of the amino-functionalized metal organic framework gel (MOF-NH2gel) mixed matrix membrane (MMMs). The MOF gel with an amino functional group is directly constructed by introducing an amino ligand in the synthesis process of the MOF gel, so that the compatibility and dispersity of the MOF gel with a polymer are remarkably improved, and the gas separation performance of MMMs is further improved. Due to the high polarity of the MOF-NH2gel and the selective adsorption capacity of the MOF-NH2gel on CO2, the CO2 permeability and selectivity of the membrane are remarkably improved. Compared with an unmodified MOF gel MMMs membrane, the modified MOF gel MMMs membrane has the advantages that the CO2 permeability and the CO2 / CH4 selectivity are respectively improved by 1.08 to 2.3 times. The method is simple, convenient and efficient, is suitable for large-scale production, has the advantages of energy conservation and environmental protection, and shows wide application potential in the field of carbon dioxide capture and separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of membrane separation technology, in particular to an amino-functionalized metal organic framework gel (MOF-NH 2 Mixed matrix membranes (MMMs) prepared by gel and their application in CO 2 Method of capture. Background Art

[0002] As industrialization and energy demand continue to grow, CO 2 Large-scale emissions have become one of the main causes of global warming. To meet this challenge, CO 2 Capture and storage (CCS) technology has become a key means to solve the problem of greenhouse gas emissions. Membrane separation technology has gradually become a CO 2 However, traditional membrane materials, such as polymer membranes and inorganic membranes, usually have significant defects in gas separation performance and long-term stability, making it difficult to meet the high-efficiency separation requirements in industrial applications.

[0003] Metal-organic framework (MOF) materials have shown great potential in the field of gas separation due to their unique pore structure, tunable pore size and high specific surface area, especially in CO 2 In terms of capture. MOF materials have good gas adsorption and separation performance, but traditional MOF materials are prone to agglomeration in polymer matrices, have poor dispersion, and have poor compatibility with polymers, resulting in insufficient mechanical strength of the membrane and unstable gas separation performance. These problems limit the application of MOF materials in actual industrial gas separation.

[0004] In order to overcome the above limitations, the present invention introduces amino-functionalized MOF gel (MOF-NH 2 The amination modification of MOF gel improves the dispersibility and compatibility of MOF materials with polymer matrices. The amination-modified MOF gel forms a three-dimensional interconnected network structure and improves the CO 2 The amination modification not only improves the chemical stability of MOF materials, but also significantly improves the CO 2 The high permeability and selectivity solve the limitations of traditional membrane materials and provide a new solution for efficient gas separation. Summary of the invention

[0005] The purpose of the present invention is to provide a MOF-NH 2 gel MMMs, the membrane has high efficiency CO 2 The separation performance is good, and the preparation method is simple and suitable for large-scale production.

[0006] To achieve the above object, the specific technical solutions of the present invention are as follows:

[0007] Step (1): using methanol as solvent, preparing a 1.04-4.24 mol / L mixed ligand solution, using 2-methylimidazole and 2-aminobenzimidazole in a molar ratio of 9:1;

[0008] Step (2): preparing a 0.13-0.53 mol / L metal ion solution using methanol as a solvent;

[0009] Step (3): Pour the mixed ligand solution into the metal ion solution, then immediately add 1.04-4.24 mol / L triethylamine solution and stir for 10-60 minutes. Wash with chloroform three times to remove the unreacted ligands to obtain MOF-NH 2 gel, which was then redispersed in chloroform to form MOF-NH 2 gel chloroform suspension;

[0010] Step (4): Dissolve an appropriate amount of polymer in an organic solvent to obtain a polymer solution, and then add the polymer solution to the MOF-NH 2 A certain amount of polymer solution was added dropwise to the gel, and the two were mixed evenly by ultrasonication and stirring to form a casting film mixed solution, which was then poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 1 to 4 days. Finally, the film was placed in a vacuum oven at 80 to 120 ° C and dried for 12 to 24 hours to obtain MOF-NH 2 gel MMMs.

[0011] In step (2) of the present invention, the metal ion solution may be Zn 2+ or Co 2+ .

[0012] In step (4) of the present invention, the polymer may be selected from polyimide, self-polymerizing microporous polymer, polybenzimidazole and the like.

[0013] In step (4) of the present invention, the MOF-NH 2 The content of gel is the MOF-NH 2 1~40wt% of the mass of gel MMMs.

[0014] In step (4) of the present invention, the polymer and MOF-NH 2 The total mass concentration of gel is 1.5-3.0wt%.

[0015] Preferably, the solvent of the film casting mixed solution is selected from chloroform and N,N-dimethylformamide.

[0016] In step (4) of the present invention, the stirring time is 12 to 24 hours.

[0017] In step (4) of the present invention, the treatment temperature of the vacuum treatment is 80 to 150° C., and the treatment time is 12 to 24 hours.

[0018] According to one aspect of the present invention, there is provided a MOF-NH 2 Application of gel MMMs in gas separation.

[0019] Optionally, the MOF-NH 2 Gel MMMs contain CO 2 Application in separation of bulk mixtures.

[0020] Preferably, the gas comprises N 2 and CH 4 At least one of.

[0021] In this application, the gas mixture is mixed with the MOF-NH 2 gel MMMs one side contacts, causing CO 2 Permeation MOF-NH 2 gel MMMs achieve gas separation effect.

[0022] Compared with the prior art, the present invention has the following beneficial technical effects:

[0023] MOF-NH of the present invention 2 Gel MMMs are prepared by combining amino-functionalized MOF gel materials with polymer matrices, which enhances the compatibility of MOF gel materials with polymer matrices and forms a more uniform dispersion structure, thereby greatly improving CO 2 At the same time, amino functionalization helps to improve the mechanical strength and stability of the membrane, allowing it to maintain excellent separation performance during long-term use.

[0024] The film-making method provided by the invention is easy to operate, has strong applicability, is suitable for large-scale production, is environmentally friendly and energy-saving, and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 For MOF-NH in Examples 1-8 2 Schematic diagram of the synthesis of gel.

[0026] Figure 2 is ZIF-8-NH in Example 1-4 2 TEM image of gel.

[0027] Figure 3is ZIF-8-NH in Example 1-4 2 Fourier infrared image of gel.

[0028] Figure 4 is ZIF-8-NH in Example 1-4 2 XRD pattern of gel.

[0029] Figure 5 is ZIF-8-NH in Example 1-4 2 gel's N 2 Adsorption diagram.

[0030] Figure 6 is ZIF-8-NH in Example 1-4 2 Pore ​​size distribution of gel.

[0031] Figure 7 is ZIF-8-NH in Example 1-4 2 CO of gel 2 Adsorption diagram.

[0032] Figure 8 The XRD patterns of the films prepared in Example 1 and Comparative Example 1 are shown below.

[0033] Fig. 9 The gas separation performance diagram of the membranes prepared in Examples 1-4 and Comparative Examples 1-5.

[0034] Fig.10 The gas separation performance diagram of the membranes prepared in Examples 5-8 and Comparative Examples 6-9.

[0035] Fig.11 The gas separation performance and upper bound comparison chart of the membranes prepared in Examples 1-8 and Comparative Examples 1-9. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below through several specific embodiments, but the present application is not limited thereto. Without departing from the content and scope of the present invention, any changes and implementations should be included in the technical scope of the present invention.

[0037] Example 1:

[0038] Step (1): using methanol as solvent, preparing a 4.24 mol / L mixed ligand solution, using 2-methylimidazole and 2-aminobenzimidazole in a molar ratio of 9:1;

[0039] Step (2): Prepare 0.53 mol / L Zn(NO 3 ) 2 6H 2 O solution;

[0040] Step (3): Pour the mixed ligand solution into Zn(NO 3 ) 2 6H 2 O solution, and then immediately add 4.24 mol / L triethylamine solution and stir for 60 minutes. Then wash with chloroform three times to remove the unreacted ligand to obtain ZIF-8-NH 2 gel, which was then redispersed in chloroform to form ZIF-8-NH 2 gel chloroform suspension;

[0041] Step (4): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then 0.02 g of ZIF-8-NH 2 A certain amount of polymer solution was added dropwise to the gel, and the two were mixed evenly by ultrasonication and stirring to form a casting film mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 9.0 wt% ZIF-8-NH 2 gel MMMs.

[0042] Example 2:

[0043] Steps (1)-(3) are the same as in Example 1

[0044] Step (4): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then 0.04 g of ZIF-8-NH 2 A certain amount of polymer solution was added dropwise to the gel, and the two were mixed evenly by ultrasonication and stirring to form a casting film mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 17.0 wt% ZIF-8-NH 2 gel MMMs.

[0045] Example 3:

[0046] Steps (1)-(3) are the same as in Example 1

[0047] Step (4): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then 0.06 g of ZIF-8-NH 2 A certain amount of polymer solution was added dropwise to the gel, and the two were mixed evenly by ultrasonication and stirring to form a casting film mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 23.0 wt% ZIF-8-NH 2 gel MMMs.

[0048] Example 4:

[0049] Steps (1)-(3) are the same as in Example 1

[0050] Step (4): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then 0.08 g of ZIF-8-NH 2 A certain amount of polymer solution was added dropwise to the gel, and the two were mixed evenly by ultrasonication and stirring to form a casting film mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 28.0 wt% ZIF-8-NH 2 gel MMMs.

[0051] Example 5:

[0052] Step (1) is the same as Example 1

[0053] Step (2): Prepare 0.53 mol / L Co(NO 3 ) 2 6H 2 O solution;

[0054] Step (3): Pour the mixed ligand solution into Co(NO 3 ) 2 6H 2 O solution, and then immediately add 4.24 mol / L triethylamine solution and stir for 10 minutes. Then wash with chloroform three times to remove the unreacted ligand to obtain ZIF-67-NH 2 gel, which was then redispersed in chloroform to form ZIF-67-NH 2 gel chloroform suspension;

[0055] Step (4): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then 0.02 g of ZIF-67-NH 2 A certain amount of polymer solution was added dropwise to the gel, and the two were mixed evenly by ultrasonication and stirring to form a casting film mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 9.0wt% ZIF-67-NH 2 gel MMMs.

[0056] Example 6:

[0057] Steps (1) to (3) are the same as in Example 5;

[0058] Step (4): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, which was then added to 0.04 g of ZIF-67-NH 2 A certain amount of polymer solution was added dropwise to the gel, and the two were mixed evenly by ultrasonication and stirring to form a casting film mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 17.0 wt% ZIF-67-NH 2 gel MMMs.

[0059] Example 7:

[0060] Steps (1) to (3) are the same as in Example 5;

[0061] Step (4): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then 0.06 g of ZIF-67-NH 2 A certain amount of polymer solution was added dropwise to the gel, and the two were mixed evenly by ultrasonication and stirring to form a casting film mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 23.0wt% ZIF-67-NH 2 gel MMMs.

[0062] Example 8:

[0063] Steps (1) to (3) are the same as in Example 5;

[0064] Step (4): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then 0.06 g of ZIF-67-NH 2 A certain amount of polymer solution was added dropwise to the gel, and the two were mixed evenly by ultrasonication and stirring to form a casting film mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 23.0wt% ZIF-67-NH 2 gel MMMs.

[0065] Example 9:

[0066] Steps (1) to (3) are the same as in Example 5;

[0067] Step (4): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then 0.08 g of ZIF-67-NH 2A certain amount of polymer solution was added dropwise to the gel, and the two were mixed evenly by ultrasonication and stirring to form a casting film mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 28.0wt% ZIF-67-NH 2 gel MMMs.

[0068] Comparative Example 1:

[0069] Dissolve 0.2 g of PIM-1 in chloroform, stir at room temperature for 24 hours to form a casting solution, pour it into a smooth and flat round glass culture dish, evaporate slowly at room temperature for 2 days, then soak the membrane in methanol for 1 day, and finally place the membrane in a vacuum oven at 80°C and dry it for 24 hours to obtain a pure PIM-1 membrane.

[0070] Comparative Example 2:

[0071] Step (1): Prepare 0.53 mol / L Zn(NO 3 ) 2 6H 2 O solution, according to Zn(NO 3 ) 2 6H 2 O: prepare the organic ligand solution with the ratio of imidazole: triethylamine being 1:8:8;

[0072] Step (2): The organic ligand solution was mixed and stirred for 60 minutes. The unreacted ligand was washed three times with chloroform to obtain ZIF-8gel, which was then redispersed in chloroform to form a ZIF-8gel chloroform suspension;

[0073] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.02 g of ZIF-8gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 9.0 wt% ZIF-8gel / PIM-1MMMs.

[0074] Comparative Example 3:

[0075] Step (1) to step (2) are the same as in Comparative Example 2;

[0076] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.04 g of ZIF-8gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 17.0 wt% ZIF-8gel / PIM-1MMMs.

[0077] Comparative Example 4:

[0078] Step (1) to step (2) are the same as in Comparative Example 2;

[0079] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.06 g of ZIF-8gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 23.0 wt% ZIF-8gel / PIM-1MMMs.

[0080] Comparative Example 5:

[0081] Step (1) to step (2) are the same as in Comparative Example 2;

[0082] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.08 g of ZIF-8gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 120°C and dried for 24 hours to obtain 28.0 wt% ZIF-8gel / PIM-1MMMs.

[0083] Comparative Example 6:

[0084] Step (1): Prepare 0.53 mol / L Co(NO 3 ) 2 6H 2 O solution, according to Co(NO 3 ) 2 6H 2 O: prepare the organic ligand solution with the ratio of imidazole: triethylamine being 1:8:8;

[0085] Step (2): Mix and stir the organic ligand solution for 10 minutes, wash the unreacted ligand three times with chloroform to obtain ZIF-67gel, and then redisperse it in chloroform to form a ZIF-67gel chloroform suspension;

[0086] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.02 g of ZIF-67gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 150°C and dried for 24 hours to obtain 9.0 wt% ZIF-67gel / PIM-1MMMs.

[0087] Comparative Example 7:

[0088] Step (1) to step (2) are the same as in Comparative Example 6;

[0089] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.04 g of ZIF-67gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 150°C and dried for 24 hours to obtain 17.0 wt% ZIF-67gel / PIM-1MMMs.

[0090] Comparative Example 8:

[0091] Step (1) to step (2) are the same as in Comparative Example 6;

[0092] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.06 g of ZIF-67gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 150°C and dried for 24 hours to obtain 23.0 wt% ZIF-67gel / PIM-1MMMs.

[0093] Comparative Example 9:

[0094] Step (1) to step (2) are the same as in Comparative Example 6;

[0095] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.08 g of ZIF-67gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 150°C and dried for 24 hours to obtain 28.0 wt% ZIF-67gel / PIM-1MMMs.

[0096] CO2 of MMMs in Examples 1-8 and Comparative Examples 1-9 at 0.1 MPa and 35 °C 2 Permeability and gas mixture for CO 2 / CH 4 The selection performance is shown in Table 1. Table 1

[0097] Through the detailed comparative analysis of the table data, it can be seen more clearly that MOF-NH 2 gel(ZIF-8-NH 2 gel and ZIF-67-NH 2 The performance of MMMs was significantly improved by the amination of ZIF-8-NH4 gel compared with the non-amination MOF gel at the same loading amount. Taking Example 4 and Comparative Example 5 as examples, both of them used a loading amount of 28.0 wt%, but the performance difference was significant. 2 CO of gel / PIM-1MMMs 2 The permeability coefficient reached 12065 Barrer, while the permeability coefficient of unaminated ZIF-8gel / PIM-1MMMs (Comparative Example 5) was 11158 Barrer, and the permeability performance was improved by about 1.08 times. 2 / CH 4 The selectivity of Example 4 reached 29.7, while the selectivity of Comparative Example 5 was only 16.5, an increase of about 1.8 times. This improvement clearly shows that the amination treatment significantly enhances the separation performance of MMMs, especially in terms of gas selectivity, showing a strong potential for improvement. Similarly, comparing Example 8 and Comparative Example 9, both of which also use 28.0wt% ZIF-67gel loading. The amination of ZIF-67gel / PIM-1MMMs in Example 8 shows CO 2The permeability coefficient is 6075 Barrer, while that of the unaminated ZIF-67 gel / PIM-1MMMs in Comparative Example 9 is only 5704 Barrer, and the permeability performance is improved by about 1.07 times. In terms of selectivity, the aminated MOF gel / PIM-1MMMs has a higher selectivity than the CO 2 / CH 4 The selectivity is 37.4, while the selectivity of the unaminated MOF gel / PIM-1MMMs in Comparative Example 9 is only 16.5, an increase of about 2.3 times. This data comparison further shows that the advantage of amination treatment in improving selectivity is particularly obvious. Under the same MOFgel loading, the amination-treated MOF gel significantly improved the separation performance of MMMs, especially showing an excellent improvement in gas selectivity. The amination-treated MOF gel reduces the agglomeration of MOF particles by enhancing the compatibility with the polymer matrix, constructs a continuous gas transmission channel, and at the same time, due to the interaction between the amino functional group and CO 2 The polar interactions significantly increased the CO 2 The adsorption selectivity of ammoniated MOF gel MMMs is improved. This dual mechanism works together, resulting in the separation performance of ammoniated MOF gel MMMs being much better than that of non-ammoniated MOF gel membranes at the same loading amount. Through the comparative analysis of the above examples, ammoniated MOFgel has shown great application prospects and innovation in membrane separation technology, especially in the field of gas separation.

[0098] The above are only several embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, using the above disclosed technical content to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. An amino-functionalized MOF gel (MOF-NH2 gel) mixed matrix membrane (MMMs) for efficient carbon dioxide separation and its preparation method and application, characterized in that: The MOF-NH2 gel MMMs comprise a polymer matrix and MOF-NH2 gel; The MOF-NH2 gel is a MOF gel modified by introducing an amino functional group (-NH2) into the MOF material structure. ; The MOF gel is selected from zinc MOF gel and cobalt MOF gel.

2. The MOF-NH2 gel MMMs according to claim 1, characterized in that: The zinc MOF gel is selected from ZIF-8gel; Preferably, the cobalt-based MOF gel is ZIF-67gel.

3. The MOF-NH2 gel MMMs according to claim 1, characterized in that: The content of the MOF-NH2 gel is 1wt% to 40wt% of the mass of the MOF-NH2 gel MMMs.

4. The MOF-NH2 gel MMMs according to claim 1, characterized in that: The polymer matrix is ​​selected from at least one of polyimide, polybenzimidazole and self-polymerizing microporous polymer.

5. A method for preparing the MOF-NH2 gel MMMs according to any one of claims 1 to 4, characterized in that: The MOF-NH2 gel MMMs are obtained by forming a mixed solution containing a polymer and IL@MOF gel into a film and subjecting the film to vacuum treatment.

6. The preparation method according to claim 5, characterized in that: After mixing the solution a containing the polymer with the solution b containing the MOF-NH2gel, the casting film mixed solution is obtained; The stirring time is 12 to 24 hours.

7. The preparation method according to claim 5, characterized in that: In the film casting mixed solution, the total mass concentration of the polymer and the MOF-NH2 gel is 1.5-3wt%; Preferably, the solvent of the film casting mixed solution is selected from at least one of chloroform and N,N-dimethylformamide.

8. The preparation method according to claim 5, characterized in that: The treatment temperature of the vacuum treatment is 80-150° C., and the treatment time is 24-48 hours.

9. Use of the MOF-NH2 gel MMMs according to any one of claims 1 to 4 or the MOF-NH2 gel MMMs prepared by the preparation method according to any one of claims 5 to 8 in gas separation.

10. The use according to claim 9, characterized in that: Application of the MOF-NH2 gel MMMs in separation of gas mixtures containing CO2; Preferably, the gas comprises at least one of N2 and CH4.

Citation Information

Patent Citations

  • Metal organic framework gel mixed matrix membrane as well as preparation method and application thereof

    CN117443208A